2018
DOI: 10.7150/thno.26249
|View full text |Cite
|
Sign up to set email alerts
|

Integration of magnetic resonance imaging and protein and metabolite CSF measurements to enable early diagnosis of secondary progressive multiple sclerosis

Abstract: Molecular networks in neurological diseases are complex. Despite this fact, contemporary biomarkers are in most cases interpreted in isolation, leading to a significant loss of information and power. We present an analytical approach to scrutinize and combine information from biomarkers originating from multiple sources with the aim of discovering a condensed set of biomarkers that in combination could distinguish the progressive degenerative phenotype of multiple sclerosis (SPMS) from the relapsing-remitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…We have here demonstrated that adding a limited number of CSF protein measurements in a model-based manner can improve the differential diagnosis. In line with this, we have recently demonstrated that integration of CSF protein, metabolite, and MRI measurements can improve differential diagnosis in multiple sclerosis [44]. Integrative diagnostics holds great potential in future diagnostic assessments, yet the challenge is to identify a limited number of markers that holds complementary information and that preferably can be acquired in a clinical setting.…”
Section: Discussionmentioning
confidence: 93%
“…We have here demonstrated that adding a limited number of CSF protein measurements in a model-based manner can improve the differential diagnosis. In line with this, we have recently demonstrated that integration of CSF protein, metabolite, and MRI measurements can improve differential diagnosis in multiple sclerosis [44]. Integrative diagnostics holds great potential in future diagnostic assessments, yet the challenge is to identify a limited number of markers that holds complementary information and that preferably can be acquired in a clinical setting.…”
Section: Discussionmentioning
confidence: 93%
“…Nuclear magnetic resonance spectroscopy-based methods have previously been used to study the CSF metabolome, comparing MS with controls and other neurological diseases [12,13,14,15,16,17]. Using high-resolution mass spectrometry (HRMS), we recently demonstrated that CSF metabolites integrated with protein and magnetic resonance imaging (MRI) information can improve early detection of SPMS [18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its proximity to the central nervous system (CNS), CSF is better for study diseases affecting the brain. Today, more than 450 metabolites have been identified and quantified in human CSF (Wishart et al 2008) and several of these have been found altered in neurological diseases, such as Alzheimer's disease (Wilkins and Trushina 2018), Parkinson's disease (Willkommen et al 2018), Huntington's disease (Herman et al 2019b) and multiple sclerosis (MS) (Herman et al 2018(Herman et al , 2019aReinke et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used non-targeted metabolomics methods of CSF to increase understanding of SPMS (Herman et al 2019a) and provided a methodology to integrate multiple layers of information to improve early detection of transitioning patients (Herman et al 2018).…”
Section: Introductionmentioning
confidence: 99%